Biotic communities : southwestern United States and northwestern Mexico - Brown, David E. (David Earl), 1938-2021 (University of Utah Press, 1994)
Biotic Communities catalogs and defines by biome, or biotic community, the region centered on Arizona, New Mexico, Sonora, Chihuahua, and Baja California Norte, plus portions of California, Nevada, Utah, Colorado, Texas, Coahuila, Sinaloa, and Baja California Sur. This ambitious guide is an essential companion for anyone working in natural resources management and ecological research, as well as nonspecialists looking for solid information about a particular southwestern locale. Biotic Communities is arranged by climatic formation with a short chapter for each biome describing climate, physiognomy, distribution, dominant and common plant species, and characteristic vertebrates. Subsequent chapters contain careful descriptions of zonal subdivisions.